STRUCTURAL CHARACTERIZATION OF TUNGSTEN CARBIDE (WC) COATINGS DEPOSITED ON 4340 STEELS BY CO2 LASER IRRADIATION - Silvelene Alessandra Silva; Vitor Ribeiro Jardim; Paulo Paiva Oliveira Leite Dyer; Getúlio de Vasconcelos (Revista UniVap, 2024)
The use of coatings that imbue high hardness to industrial tools, becomes a maintenance cost management strategy. Considering the coating capacity to increase the part lifespan, especially the cutting tools and those that are subjected to high degrees of physical and thermal variation stress. Consequently, in recent years the research and development of industrial coatings has grown, aiming the application of coatings with high hardness for cutting tools with metal matrices to form composites. In this sense, tungsten Carbide (WC) coatings are one of the most used in power generation systems, aerospace, automotive and transportation industry due to their properties, which combine high hardness and wear resistance. The present work aims to verify the improvement in mechanical properties of the AISI 4340 steel through the deposition of WC coating sprayed by pneumatic gun and subsequent CO2 laser irradiation. The specimens were characterized by scanning electron microscope, optical microscope and micro-indentation test (microhardness and elasticity modulus measurements). The results show that it is possible to obtain coatings with high hardness, without pores and metallurgically bound to the substrate